PENGARUH KOMITMEN ORGANISASIONAL DAN SIKAP PADA BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI MALUKU - Asthenu, Jean Rosalina (Fakultas Ekonomi Universitas Wisnuwardhana, 2013)
This study aims to identify: how organizational commitment, organizational culture on attitudes towards employee OCB Office of Industry and Trade of the Province of Maluku, as well as how the influence of organizational commitment on organizational culture and attitudes towards employee OCB Office of Industry and Trade of the Province of Maluku. The object of this study are organizational commitment, organizational culture and attitudes on OCB. The study was conducted at the Department of Industry and Trade of Maluku province, with the number of respondents with 55 employees at the Department of Industry and Trade of the Province of Maluku. Testing hypotheses using path analysis (path analysis) which is equipped with testing the validity and reliability. Based on the analysis of the model lines of research, obtained results that organizational commitment on organizational culture and attitudes simultaneously significant effect on OCB.Key words: organizational commitment, attitude on organizational culture, OCB.